Surface morphology evolution during plasma etching of silicon: roughening, smoothing and ripple formation. (15th September 2017) - Ono, Kouichi; Nakazaki, Nobuya; Tsuda, Hirotaka; Takao, Yoshinori; Eriguchi, Koji
Abstract: Atomic- or nanometer-scale roughness on feature surfaces has become an important issue to be resolved in the fabrication of nanoscale devices in industry. Moreover, in some cases, smoothing of initially rough surfaces is required for planarization of film surfaces, and controlled surface roughening is required for maskless fabrication of organized nanostructures on surfaces. An understanding, under what conditions plasma etching results in surface roughening and/or smoothing and what are the mechanisms concerned, is of great technological as well as fundamental interest. In this article, we review recent developments in the experimental and numerical study of the formation and evolution of surface roughness (or surface morphology evolution such as roughening, smoothing, and ripple formation) during plasma etching of Si, with emphasis being placed on a deeper understanding of the mechanisms or plasma–surface interactions that are responsible for. Starting with an overview of the experimental and theoretical/numerical aspects concerned, selected relevant mechanisms are illustrated and discussed primarily on the basis of systematic/mechanistic studies of Si etching in Cl-based plasmas, including noise (or stochastic roughening), geometrical shadowing, surface reemission of etchants, micromasking by etch inhibitors, and ion scattering/chanelling. A comparison of experiments (etching and plasma diagnostics) and numerical simulations (Monte Carlo and classical molecular dynamics) indicates a crucial role of the ion scattering or reflection from microscopically roughened feature surfaces on incidence in the evolution of surface roughness (and ripples) during plasma etching; in effect, the smoothing/non-roughening condition is characterized by reduced effects of the ion reflection, and the roughening-smoothing transition results from reduced ion reflections caused by a change in the predominant ion flux due to that in plasma conditions. Smoothing of initially rough surfaces as well as non-roughening of initially planar surfaces during etching (normal ion incidence) and formation of surface ripples by plasma etching (off-normal ion incidence) are also presented and discussed in this context.